Is Romania a Favourable Environment for the Development of Knowledge-Based Organizations? - Adela Anca FUCEC (Revista de Management Comparat International)
The Europe 2020 Stategy enhances the European Union’s efforts to achieve sustainable economic growth, by transforming the economies of the member states in knowledge-based economies. This strategy aims at five major objectives that relate to unemployment, research and development, energy, education, poverty and social exclusion. Using the 8 indicators which measure these developments, this article aims to achieve an informational synthesis with a tolerable loss of information and to obtain an aggregate indicator, which will help at a graphical representation or a hierarchization of the countries analyzed. Using the Principal Components Analysis, we used the values of the 8 indicators registered in the EU countries, plus Switzerland, Norway and Iceland, in 2010; two indicators that give about 95% of initial information have been found and it now becomes possible to rank the countries in terms of their evolution towards the stage of a knowledge-based economy. Thus, we get the answer to the question-title, discovering Romania's position in the European landscape of knowledge-based economies, by having achieved the ranking of the countries.